2021
DOI: 10.1136/bmjopen-2020-048212
|View full text |Cite
|
Sign up to set email alerts
|

CoronaCare study protocol: an ethnographic study of the risks to and potential for social health during the COVID-19 pandemic

Abstract: IntroductionGerman government regulations such as physical distancing and limited group numbers, designed to curb the spread of COVID-19, have had far-reaching consequences for the very foundations of social life. They have, to name only a few, transformed greetings and goodbyes, blurred private and public worlds, and complicated basic communication with mandatory mask wearing. The ethnographic study CoronaCare investigates how these sociopolitical measures affect social health, a form of health which unfolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
2
Order By: Relevance
“…Interestingly, in this study, it was found that the health protocol, which is a new culture campaigned by the government, did not affect employee job satisfaction. This is because the application of health protocols aims to prevent the transmission of COVID-19 in the workplace (Paul et al, 2021;Schieman et al, 2021). The implementation of the health protocol is to enable them to perform even with limited conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in this study, it was found that the health protocol, which is a new culture campaigned by the government, did not affect employee job satisfaction. This is because the application of health protocols aims to prevent the transmission of COVID-19 in the workplace (Paul et al, 2021;Schieman et al, 2021). The implementation of the health protocol is to enable them to perform even with limited conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Work from home is a form of change made to reduce the number of Covid-19 infections in the workplace and the application of health protocols in the workplace (Putri & Amran, 2021;SandovalReyes et al, 2021;Paul et al, 2021;Schieman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…CoronaCare ist eine ethnografische Studie, in der unter anderem im Abstand von drei Monaten regelmäßig ethnografische Interviews mit ausgewählten Bürger*innen durchgeführt werden. Das Studiendesign ist in Paul et al ausführlich dargestellt und öffentlich zugänglich [5].…”
Section: Studiendesignunclassified
“…Die aktuelle Covid-19 Pandemie wurde von der WHO als solche im März 2020 deklariert 4 . Den Spannungen und Herausforderungen, die durch die Eindämmung der Transmission von SARS-CoV-2 entstehen, geht die ethnografische Studie CoronaCare nach, die seit März 2020 Daten von Menschen in Deutschland zu ihrem alltäglichen Leben erhebt 5 . Sie untersucht, welche Auswirkungen die politischen Maßnahmen zur Eindämmung der Covid-19 Pandemie in der Bundesrepublik Deutschland auf die soziale Gesundheit der Menschen haben.…”
Section: Einleitung/hintergrundunclassified